A critical evaluation of subjective ratings: Unacquainted observers can reliably assess certain personality traits. Issue 2 (1st April 2014) - Petelle, Matthew B.; Blumstein, Daniel T.
Abstract: Methods to measure consistent individual differences in behavior (i.e. animal personality) fall into two categories, subjective ratings and behavioral codings. Ratings are seldom used despite being potentially more efficient than codings. One potential limitation for the use of ratings is that it is assumed that long-term observers or experts in the field are required to score individuals. This can be problematic in many cases, especially for long-term ecological studies where there is high turnover in personnel. We tested whether raters who were unacquainted with subjects could produce reliable and valid personality assessments of yellow-bellied marmots Marmota flaviventris . Two raters, previously unacquainted with individuals and marmot behavior, scored 130 subjects on fifteen different adjectives in both open-field (OF) and mirror image stimulation (MIS) trials. Eight OF and nine MIS adjectives were reliable as indicated by both a high degree of intra-observer and inter-observer reliability. Additionally, some ratings were externally valid, correlating with behavioral codings. Our data suggest that activity/exploration and sociability can be a reliable and valid measurement of personality traits in studies where raters were unacquainted with subjects. These traits are observable with the personality tests we used; otherwise researchers using unacquainted raters should be cautious in the tests they employ.